Numerical software verification : 12th International Workshop, NSV 2019, New York City, NY, USA, July 13-14, 2019 : proceedings /: 12th International Workshop, NSV 2019, New York City, NY, USA, July 13-14, 2019 : proceedings. ([2019]) - Unknown
No abstract available